Synaptic elimination by microglia and disturbed higher brain functions. (January 2021) - Miyanishi, Kazuya; Sato, Arisa; Kihara, Nanako; Utsunomiya, Ryo; Tanaka, Junya
Abstract: Microglial cells in normal mature brains have long been considered to be cells that are resting until pathological events take place, activating the microglial cells. However, it is currently well known that the microglia that have resting ramified morphology in normal mature brains move actively in the brain parenchyma and phagocytose synapses, thus forming and maintaining neural circuits. This review summarizes recent findings on the roles of microglia in mature brains, with special reference to phagocytosis of synapses and higher brain functions. Phagocytic elimination of synapses by microglia may affect the balance between excitatory and inhibitory synaptic transmission, termed the E/I balance. When impaired synaptic elimination by microglia leads to disturbed E/I balance, various problems may follow in brain functions: in memory and cognitive functions, sleep, movement, social behaviors, and thinking. In addition to the roles of microglia in normal developing and mature brains, impaired microglial phagocytosis functions also correlate with disturbances to these higher brain functions that are caused by neurological, mental, and developmental disorders; Parkinson's and Alzheimer's diseases, autism spectrum disorder, attention deficit/hyperactivity disorder, and schizophrenia. Highlights: Microglia engage in synaptic elimination by phagocytosis in mature brains. Selective synaptic elimination changes excitatory/inhibitory (E/I) balance. Microglia modulate neuropsychiatric disorders by synaptic elimination. This review discusses Parkinson's and Alzheimer's diseases, ASD, ADHD, and schizophrenia.